The volatile tale of arabidopsis thaliana: enhancing plant growth and salinity stress tolerance by overexpressing α-acetolactate decarboxylase to produce acetoin in planta - Rust, Catharina Magdalena (Carlien) (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.